Implementasi Ubiquitous Computing Berbentuk Aplikasi Buku Tamu di SMK N 3 Payakumbuh sebagai Dukungan terhadap Komitmen SMK Berinovasi - Agus Nur Khomarudin; Romy Aulia; Rina Novita; Indra Laksmana; Jamaluddin, Jamaluddin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The application of ubiquitous computing has been widely used, the field of education is also not immune from the impact of ubiquitous computing advances, seen with many learning processes that use mobile devices and easy, flexible and real-time administrative management. SMK N 3 Payakumbuh as one of the educational institutions is committed to continuing to innovate, understanding the importance of adopting technology in supporting operational efficiency and effectiveness. Currently, PkM partners still rely on manual methods in recording guests who come to the school. This process involves manually filling in the guest book by the school administration officer. This manual method is prone to recording errors, difficult to track, and time-consuming. This is the background for holding a community service, in this context is the school community with an idea or creative idea, namely the creation and application of a QR Code-based guest book. The PkM method used is partner assistance, with 3 stages which include: preparation, implementation and evaluation of PkM activities. The application of the QR-Code-based guest book in this PkM can be conveyed that PkM products are very helpful for partners in committing to realizing Innovative Vocational Schools. In addition, there are hopes from PkM partners, namely: so that this activity continues in the coming semester with other forms of innovation.